Silagem de grãos úmidos de milho na alimentação de frangos Label Rouge com suplementação de acidificante - Frank, Rafael (2014)
The objective of this study was to determine the aerobic stability, centesimal composition and energy values and the amino acids digestibility of high moisture corn grain silage (HMCS), and evaluate the effect of HMCS inclusion in different levels in diets on performance and gut parameters of Label Rouge broilers. In Experiment 1, to determine the applicability of inoculants usage the growth of main microorganisms involved in fermentation of high moisture corn grain silage was evaluated among time periods, as well as aerobic stability when silages were made with or without the addition of inoculum Lactobacillus plantarum + Propionibacterium acidipropionici. Significant changes were observed for temperature and pH as a function of storage time and use of inoculum. For the population of fungi and entero-bacteria a significant decrease in function of the storage time was observed more expressive for silages in which the inoculum was applied. Changes in all populations of microorganisms studied as a function of storage time were observed. For the chemical composition differences were obtained for dry matter, neutral detergent fiber and acid detergent fiber, when we used silage additive and changes in the concentration of acid detergent fiber in function of the different storage times. Aerobic stability was of 156 hours for silage ensiled by 28 days, without significant difference for inoculation. When ensiled for 56 days, the silage inoculated presented greater stability (60 hours) when compared to no inoculant (32 hours). The high moisture grain corn silage with microbial inoculum based on Lactobacillus plantarum and Propionibacterium acidipropionici was able to reduce the population of fungi and enterobacteria. In Experiment 2, to determine the energy values of high moisture corn silage (HMCS), male broilers from 21 to 31 days old were used, averaging 765 ± 1.70 g. The experimental period lasted ten days, five of adaptation and five for collection. The HMCS replaced in 10, 20, 30 and 40% the reference ration (RR). The method of analysis was the total excreta collection for subsequent analysis of apparent metabolizable energy (AME) and AME corrected for nitrogen balance (AMEn) of HMCS. To determine the amino acid values, the technique of forced feeding was applied in 12 cecectomized Leghorn roosters, with average weight of 1912.10 ± 133.73 g. Six animals received HMCS and the other six were fasted. At the end of the excreta collection period, the essential amino acid profile was determined, as the true digestibility coefficients and the true digestible content of amino acids in HMCS. This food presented average values of 2283 kcal/kg of EMA and 2272 kcal/kg of AMEn, and these energy values were negatively influenced by the inclusion levels of HMCS. Cystine presented the lower digestibility coefficients while leucine and glutamine had the highest digestibility and digestible amino acids values. In Experiment 3, one thousand and two hundred Label Rouge chicks with an average initial weight of 41 ±0.55g were distributed in a completely randomized design, in a factorial 2x5 (with and without the addition of acidifying X 0, 25, 50, 75 and 100% of high-moisture corn grain silage - HMCS). The weight gain (WG), feed intake (FI) and feed conversion (F:G) were determined, beyond the intestinal morphometric analysis and microbiota, carcass yield and cuts. From 1-28 and 1-63 days there was a quadratic effect (P<0.05) of HMCS on FI and F:G. There was interaction (P<0.05) between the levels of HMCS and the addition of acidifying for carcass yield and cuts (wing and chest) and liver of females. Males presented interaction (P<0.05) between levels of HMCS and acidifying for carcass, drumstick, chest and fat. There was an interaction (P<0.05) between HMCS and the inclusion of acidifying in the counting of Lactobacillus and Clostridium at 28 days old and for Lactobacillus at 63 days old. At 28 days there was an interaction (P<0.05) between HMCS and the inclusion of acidifying for villi height. At 63 days there was and quadratic effect of HMCS and the acidifying for crypts, which presented higher diameter for treatments without acidifying. The results suggest that jerk chickens fed up to 50% of HMCS with acidifying had good carcass yield and cuts and had no damage on intestinal development